Does the etiology affect the outcome and satisfaction rates of penile prosthesis implantation surgery? - Ibrahim Halil Bozkurt; Burak Arslan; Zafer Kozacioglu; Tarik Yonguc; Tansu Degirmenci; Bulent Gunlusoy; Suleyman Minareci (Kaohsiung Journal of Medical Sciences, 2014)
Our aim was to compare the outcomes and satisfaction rates of men undergoing penile prostheses implantation (PPI) secondary to radical prostatectomy (RP) and other causes of vasculogenic erectile dysfunction (ED). A total of 142 patients, of whom 60 underwent PPI due to ED following RP (Group 1) and 82 underwent PPI due to ED with other vasculogenic causes (Group 2) were included in this study. The preoperative erectile status was evaluated with the International Index of Erectile Function (IIEF). The satisfaction of patients and partners were evaluated by a telephone interview using Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) questionnaire and Erectile Dysfunction Inventory of Treatment Satisfaction Partner Survey. Preoperative mean IIEF scores were significantly lower in Group 1 (17.5 ± 6.4 vs. 24.2 ± 5.1, p = 0.01). For Groups 1 and 2, the mean EDITS scores of the patients were 58 ± 10 and 71 ± 8, respectively, and that for the partners were 46 ± 8 and 65 ± 7, respectively. Group 1 had significantly lower scores both for the EDITS and the EDITS Partner Survey (p = 0.03, p = 0.01, respectively). Patients who had undergone RP and their partners were found to have lower satisfaction rates compared to patients with other causes of vasculogenic ED who had penile implant surgery. From this point of view, it is important to know the patient's expectations about the treatment outcomes and a preoperative psychological and sexual counseling should be managed for possible treatment alternatives after RP.